Smart Aquaponics: Iot-Integrated Biofiltration In NFT Systems For Sustainable Food Production - Massaty, Muhammad Hassan; Andrian, Dimas Pamilih Epin; Fahrurozi, Slamet Kurniawan (Jurnal Ilmiah SINUS, 2026)
This study presents the design and evaluation of an IoT-enabled aquaponic system based on the Nutrient Film Technique (NFT) with integrated bio-mechanical filtration for sustainable food production. Three configurations were tested: NFT 1 (100 fish with bio-mechanical filtration), NFT 2 (50 fish with bio-mechanical filtration), and NFT 3 (50 fish with mechanical filtration only). Automated monitoring using a NodeMCU microcontroller with pH, TDS, temperature, and water-level sensors enabled real-time data transmission to Thingspeak. Over 30 days, NFT systems with bio-mechanical filtration (NFT 1 and NFT 2) maintained stable water quality (pH 6.0–6.8, TDS within tolerance), whereas NFT 3 showed sharp fluctuations and dissolved solids accumulation (up to 280 ppm). Plant growth (Ipomoea aquatica) was highest in NFT 1 (28.5 cm, 30.0 g), while NFT 3 performed poorest. Tilapia growth was also greatest in NFT 1 (50.3 g), though NFT 2 demonstrated superior feed efficiency. These results underscore the pivotal role of biofiltration in stabilizing water quality, enhancing resource efficiency, and supporting integrated aquaponic productivity in IoT-based systems